The Ripple Effects of Maritime Piracy and Armed Robbery in the Gulf of Guinea - Boateng, Nana (Advances in Social Sciences Research Journal, 2021)
The acts of piracy had bedeviled mankind for many centuries though the modus operandi of this sinister act keeps changing over the years. The core concept still remains the same. It usually involves an armed attack at sea for a vessel, its cargo, crew or all of the three. The stage is set at sea, but the fall out effects are far reaching than we can imagine. There are political, economic social, security and environmental implications. All these aggregates or determinants are intertwined and have adverse consequences on all the stakeholders. Failed states political instability has become fertile grounds for pirates or sea armed robbers. Economically, the disruption of free movement of vessels, capture of crew for ransom has adversely affected the prices of goods at its final destination. This paper seeks to examine the relationships and effects these attacks have on the various facets of the marine logistic chain. The socio-economic model of Dr Kenneth McLeroy is used to explain the various linkages existing between these determinants viz economic perspective, social perspective, environmental perspective and political instability. Finally, the relevance of maritime security in the sphere of governance and the ability of institutions which would use the safety of our oceans is examined.